Calculus Eleventh edition - Thomas, George B; Giordano, Frank R; Hass, Joel; Weir, Maurice D (New York, USA Rearson, 2008)
this edition helps students successfully generalize and apply the key ideas of calculus through clear and precise explanations, clean design, thoughtfully chosen examples, and superior exercise sets. Thomas offers the right mix of basic, conceptual, and challenging exercises, along with meaningful applications. This significant revision features more examples, more mid-level exercises, more figures, and improved conceptual flow
"Not for sale in the U.S.A. or canada"
12
Keywords: Probabilities; Statistics -- Graphic methods